Fortaleza mestiça: aquém dos ideais, além das saudades - Nogueira, João Lucas Vieira (2019)
This paper aims to analyze the discourse by which the relevance of these buildings is affirmed, from the reading of the Tipping Instructions of some culturally important buildings in Fortaleza, Ceará. It intends to show how these discourses are built from outdated theories since they belong to other cultural contexts that have nothing to do with the locals. These theories simply transplanted and applied in the readings of local buildings generate a conceptual deformity to the point that some justifications for protection have a contrary effect on everyday practice. It then seeks to build another narrative, understanding the baroque forms of mestizaje in Latin America. This baroque-mestizo is presented in culture, in the forms of production and interaction between subjects, things, and practices. It is based on a festive logic, founded on excess and waste, in direct contact with nature, made by climbing and twisting its spirals, composing a divergent, multiple and chaotic mosaic, through a rhythmic, playful and erotic character of its representatives. It noticed that these outdated readings start from an architecture-dependent on the look and thought, which materialize through the realization of the project, symbolic abstraction that marks the rupture between mind and body in architectural creation. On the other hand, in baroque-mestizo processes, architecture has been done in the realm of voice, through the relationship between bodies and gestures in a doing that is completed while speaking. It’s a process that has everything to do with the logic of the party. It is intended that this proposed understanding of architecture in Latin America can be applied not only in the practice of heritage protection but as a support for the formation of new architects who can, from a Latin American understanding of their architecture in their context. contribute to a path of trans colonization for the refinement of a systemic memory and autonomy in Latin America